Crescimento e fotossíntese de Carapa surinamensis Miq. (Meliaceae) em resposta à elevada concentração de CO 2 e déficit hídrico - Oliveira, Marcilia Freitas de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2016)
Many models have been made aiming to predict how climate change can influence the physiology of trees. Most studies, however, have concentrated on temperate regions. Few studies have been made to show how increases in CO 2 concentration and changes in water regimes can influence the functioning of tropical tree species, particularly in the Amazon. The Amazon forest is very important in the carbon cycle and the regional water regime, so it is important to know how the water regime and ambient CO 2 increase can affect this forest. Therefore the objectives of this study were to determine how the enrichment with CO 2 and water deficit can affect photosynthetic parameters and biomass gain in Carapa surinamensis Miq. The study was conducted in a growth chamber and greenhouse at the National Institute for Research in the Amazon (INPA) in Manaus-AM. The following treatments were applied: two levels of CO 2 (400 - current and 700 ppm - estimate for 2100) and two water regimes (soil with 100 and 50% of field capacity). The high CO 2 treatments were conducted in a growth chamber and ambient CO 2 treatment in the greenhouse. The experiment began with plants at the age of six months and lasted 163 days. They were determined parameters of gas exchange, growth and biomass gain of plants. Plants grown at high CO 2 experienced no acclimation of photosynthesis, which shows that future increase in CO 2 will cause positive impact on photosynthetic rates. This is because it found that photosynthesis of plant subjected to 700 ppm CO 2 increased by 100%, and the biomass gain was 62% higher than in plants grown at ambient CO 2 (400 ppm). In addition, water-use efficiency increased by 200% in plants grown under elevated CO 2 (700 ppm), which mitigated the effects of the drought stress. Water stress led to decrease in biomass production (54%) and reduction of leaf area by 47%, but it increased the in whole-plant water-use efficiency by 35%. These results are consistent with models that predict that further increase in atmospheric CO 2 may enhance the role of the Amazon forest as a carbon sink at a global scale.
Keywords: Andiroba; Mudanças climáticas; Restrição hídrica; Trocas gasosas; Biomassa